Factors Affecting English Speaking Anxiety of Students Majoring in English, Faculty of Humanities, Mahamakut Buddhist University - Sīlasampanno), Phrakittisarasuthee (Cherdchai; Sinak, Sanit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 13 No 1 (2021): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This research aimed to study factors affecting speaking English anxieties and to study the level of speaking English anxieties of students studying in the Bachelor of Arts program in English, Bachelor of Arts (English). The population was 48 students studying in the Bachelor of Arts program in English, Bachelor of Arts (English). The instrument used for data collection was a three sectioned questionnaire. Data were analyzed for percentage, mean and standard deviation. The findings of the study indicate that: 1. Factors affecting anxiety in the English conversation of students studying in the Bachelor of Arts program in English, Bachelor of Arts (English) indicate that students have anxieties if they do not pass English conversation courses is at a high level 2. Levels of anxiety in the English conversation of students is at a high level too.